Pengaruh Metode SQ4R terhadap Keterampilan Membaca Teks Eksposisi Siswa Kelas VIII SMP Negeri 3 Batang Anai - Pakpahan, Sukma Wijaya S.; Atmazaki, Atmazaki (Lembaga Yasin AlSys, 2023)
Students' reading comprehension skills are influenced by several factors, namely learning methods, student interest, and the media used by the teacher. There needs to be a method that can improve students' reading comprehension skills. This study aims to determine the significant effect of reading comprehension skills of exposition text at SMP Negeri 3 Batang Anai before and after the SQ4R method is applied. This research method is experimental research, with One Group Pretest-Posttest Design. The research population was the VIII grade students of SMP Negeri 3 Batang Anai, with the VIII grade population totaling 149, and the sample of class VII.6 with the consideration that the class was the most homogeneous because it had the lowest standard deviation, which was 12.34. The sample was drawn using purposive sampling technique. The data on reading comprehension skills of exposition texts were examined and given a score and then analyzed by t-test. The combined standard deviation of the data on reading comprehension skills of exposition texts of class VIII students of SMP Negeri 3 Batang Anai was 71.45. The results showed that because tcount> ttable (3.74>1.67). Based on the results of the study, it can be concluded that there is a significant difference in the reading comprehension skills of exposition texts of grade VIII students of SMP Negeri 3 Batang Anai before and after using the SQ4R method.